Nota preliminar - Editorial, Consejo (Cuyo. Anuario de Filosofía Argentina y Americana, 2020)
Presentación de la Revista CUYO, Anuario de Filosofía Argentina y Americana. Sus objetivos, política editorial y calidad académica alcanzada. Presentation of the Magazine CUYO, Yearbook of Argentine and American Philosophy. Its objectives, editorial policy and academic quality achieved.